Satisfaction with Life, Happiness, and Inequality – a Pseudo-Panel Study - Søren Jensen; Peder J. Pedersen (Institute of Labor Economics (IZA), 2020)
The hypothesis tested in this paper is whether the increasing inequality in recent years has had a significant impact on well-being among the population in Denmark. After a survey of the literature we use attitude variables from the European Social Survey in a pseudo-panel setting covering the years 2002 – 2014. We cover respondents from Denmark and supplement the survey data with variables from administrative registers. We find a significant effect from the increasing Gini coefficient since 2002.
Keywords: D31; H53; I31; 330; pseudo-panel; well-being; inequality